Age at First Conception and its Determinants of Ever-Married Women in Bangladesh: Conception in Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2021)
Age at first conception is an important part of the reproductive process that identifies the level of fecundability and indicative fertility during the early stages of marriage. This study explores the age at first conception and its determinants of ever-married women in Bangladesh by extracting the recent Bangladesh Demographic and Health Surveys (BDHS 2017) data. Descriptive statistics, ANOVA, chi-square tests, and binary logistic regression analysis were carried out to analyze data. Overall, the mean age at first conception of Bangladeshi women is 17.82 ± 3.29 years with significant variations by different socio-demographic, cultural, and behavioral factors. Bivariate analysis of chi-square tests shows that all the independent variables have a significant effect on age at first conception. The finding of the binary logistic regression analysis revealed that respondents’ current age, age at first cohabitation, respondents’ education, and partners’ education are the most important determinants of age at first conception in Bangladesh. Moreover, secondary (OR= 0.743, 95% CI = 0.622- 0.886, P < 0.01) and higher educated women (OR= 0.838, 95% CI = 0.710- 0.989, P < 0.05) were respectively less likely to having first conception at age above 17.25 years, compared to no educated women. Thus, to increase the age at the first conception and reduce the level of fertility, it is necessary to increase the age at the first marriage of the respondents and the level of education for both partners.